The Malaysian Nasi Lemak Story as Reviewed Online: A Genre Perspective - Anthony Thane, Angelicia (SARE: Southeast Asian Review of English, 2023)
As a multiracial country, food is a significant component of the Malaysian culture. Local cuisines serve to portray the different ethnicities which make up its population. Reflecting the nation’s unique identity, Malaysian Heritage Food (MHF) has become internationally acclaimed due to the rise of the digital era. The Internet has enabled easy access to information on various local and international cuisines, ranging from personal food vlog channels to dedicated culinary expert websites. The quest and appreciation for famous cuisines and technological convenience give rise to a relatively prominent digital genre: online food reviews, a significant source of information for gastronomes worldwide. Thus, this paper explores online food reviews focusing on Nasi Lemak, a specific MHF Malay cuisine and Malaysia’s national dish. Employing a genre perspective, I investigate the roles of text and visuals in these reviews to make sense of the form, function and meaning of this digital genre. This paper establishes the interdependence and integration between the textual and visual modes to decipher the online representation of Nasi Lemak in a Malaysian context and the digital space. The online Nasi Lemak review as a genre illustrates the significance of its multimodal nature in describing the Nasi Lemak story, simultaneously offering potential early insights into the sociocultural nuances surrounding this MHF.